'Days with snow': an appraisal of snowfall records made by Climatological Observers Link members. (21st October 2020) - Mayes, Julian
Abstract : This article is an analysis and appraisal of the snow observation records made by COL observers at 14 sites across the UK since the 1960s. There has been a substantial decline in the number of days with sleet or snow falling and particularly of days with lying snow, especially in the core winter season. The role of changing synoptic conditions is discussed, highlighting the contrast between Scotland and the rest of the UK in 'westerly' winters.